Water places, ”Tulla” and ”Cinna” of the Chalbi in the understanding of past and present socio-ecological changes. - (:unkn) unknown (My University, 2022)
In many Arid and Semi-Arid Lands, ecosystem services are often correlated with natural resources on which the livelihoods of the inhabitants depend. Most of the inhabitants have developed specific systems of production to allow an efficient use of scarce resources available. Although these local societies and ecological systems have from the past to present responded to the variability of climatic condition, they have recently experienced a shift from the implementation of various models for protection of natural resources in order to conserve biodiversity and scarce resources (water, soil, pasture, forest) to the merging of megaprojects. Current political and economic changes led international institution, government and investor development to invest in global water reform and on building infrastructure to extract new energy sources (oil, wind, hydroelectric) to the exclusion of pastoralist rangelands and water points. These processes contribute to the merging of competitive vision of nature and the erosion of their environmental consciousness, and in fine to the conservation of some specific ecological niches. Adopting a landscape approach and an interdisciplinary perspective crossing anthropology, GIS and archaeology, the contribution aims to show how the wetland (oases, "tulla wells system", etc.) in arid areas inform us about temporal and spatial dynamics of human-landscapes interactions. Focusing on the past and present socioecological changes of specific ecological niches (oases, water points, rivers, riverine forest, etc.) located in arid east African landscapes. From a set of watering places connecting important cultural, archaeological and ecological features, we explain how an ethnography of the "Tulla system" led us to mobilise GIS in order to understand the relationship between some specific social and cultural values of water, archaeological and ecological data. With regards to the state of the art, a better knowledge of the socio-ecolog
Keywords: African Research